1996
DOI: 10.1063/1.115783
|View full text |Cite
|
Sign up to set email alerts
|

Na-induced effects on the electronic structure and composition of Cu(In,Ga)Se2 thin-film surfaces

Abstract: X-ray and UV photoelectron spectroscopy measurements of Cu(InGa)Se2 thin films grown on Mo coated soda-lime glass show segregation from the substrate and formation of two different Na species. One of these species is also identified after deliberate deposition of metallic Na. Moreover, the adsorption (or segregation) of this species reduces the native oxide SeO2, while the other, reacted Na species coexists with SeO2. Small amounts of Na (≤0.05 Å) induce a band bending and reduce the surface dipole. These find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 7 publications
5
60
3
Order By: Relevance
“…The former is due to the well-known diffusion of Na from the soda-lime glass substrate through the Mo and CIGSe layers, 13 the latter indicates an IMN-to-UNLV sample transfer with minimal sample contamination. Upon In 2 S 3 deposition, S-related peaks can also be observed.…”
Section: ͑͒mentioning
confidence: 99%
“…The former is due to the well-known diffusion of Na from the soda-lime glass substrate through the Mo and CIGSe layers, 13 the latter indicates an IMN-to-UNLV sample transfer with minimal sample contamination. Upon In 2 S 3 deposition, S-related peaks can also be observed.…”
Section: ͑͒mentioning
confidence: 99%
“…Ar þ ion sputtering 6 or wet chemical treatments, 27,28 it is reported that [while stored at room temperature under ultrahigh vacuum (UHV) conditions] Na reappears again at the CIGSe surface within days. 6 3. Na affects the reaction mechanism of absorber formation [29][30][31] and hence the grain size, morphology, and texture of the CIGSe layer.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 After removing Na from the CIGSe surface by means of, e.g. Ar þ ion sputtering 6 or wet chemical treatments, 27,28 it is reported that [while stored at room temperature under ultrahigh vacuum (UHV) conditions] Na reappears again at the CIGSe surface within days. 6 3.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations